2016
DOI: 10.1017/s1751731115001998
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat quality traits of chickens fed diets concurrently supplemented with vitamins C and E under constant heat stress

Abstract: The objective of this study was to determine if a diet supplemented simultaneously with vitamins C and E would alleviate the negative effects of heat stress, applied between 28 and 42 days of age, on performance, carcass and meat quality traits of broiler chickens. A total of 384 male broiler chickens were assigned to a completely randomized design, with a 2 × 3 factorial arrangement (diet with or without vitamin supplementation and two ambient temperatures plus a pair-feeding group) and 16 replicates. Chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
55
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 36 publications
14
55
3
Order By: Relevance
“…Moreover, Hosseini-Vashan et al (2016) reported no effect of HS on the abdominal fat content of broilers. Nevertheless, our data were in contrast to Zeferino et al (2016), who showed negative effects of HS on the carcass composition and meat quality in broilers. The exact reason for the lack influence of HS on carcass traits in broilers is unclear, but the acclimatization of birds to chronic HS seemed to improve their heat tolerance (Al-Fataftah and AbuDieyeh, 2007), resulting in less alteration of metabolism and thus carcass composition.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, Hosseini-Vashan et al (2016) reported no effect of HS on the abdominal fat content of broilers. Nevertheless, our data were in contrast to Zeferino et al (2016), who showed negative effects of HS on the carcass composition and meat quality in broilers. The exact reason for the lack influence of HS on carcass traits in broilers is unclear, but the acclimatization of birds to chronic HS seemed to improve their heat tolerance (Al-Fataftah and AbuDieyeh, 2007), resulting in less alteration of metabolism and thus carcass composition.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, HS was associated with the reduced weight of active organs such as heart and intestine. This result was similar to that reported by Sohail et al (2013) and Zeferino et al (2016). Apart from the physiological adjustment derived from depressed feed intake (Zeferino et al, 2016), the increased corticosterone level in HS broilers may be responsible for the lower percentage of the organs (Hu et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, that study was not carried out in stressful conditions. In contrast, Zeferino et al (2016) in the study on chickens found that diet supplementation with vitamins C and E as antioxidants did not mitigate any of the negative effects occurring under heat stress.…”
Section: −1mentioning
confidence: 76%